Modelling the Factors Influencing Urban Households Food and Nutrition Security Status - Dorothy Thompson; Nsikak-Abasi Etim; NseAbasi Etim (Journal La Lifesci, 2020)
There was a rapid migration from poor rural areas to swollen urban areas in search of better jobs and life. While some local immigrants have managed to find a better life, most immigrants cannot guarantee the improvement of the quality of life as they hoped. It has become a nightmare of economic and food insecurity. A study was conducted to determine factors affecting food availability, accessibility and affordability for families in Akwa Ibom State, Nigeria. A survey is used to obtain information from 240 households. The Food insecurity Index is used to analyze the state of food insecurity in the study area. Foster, Greer, and Thorbecke (FGT) weighted poverty index was adopted to analyze the incidence and severity of Hunger. Tobit Regression Model is used to analyze household food security determinants. Results of analyses show that hunger is lower in families of skilled workers and higher in families with unskilled workers. The result further showed that the incidence of food insecurity and hunger was 0.61 and directly related to family size. The most critical factors influencing food security are education level, household income level, family size, access to credit facilities, distance to the nearest market, and location of residence. Policies aimed at improving living standards in rural areas are wise policy decisions to prevent conquest of the village.